identify one way to rewrite the expression using distributive property

(8x10)+(8x1)

(8x20)-(8x1)

(8x20)-1

(8x10-(8x1)

Question 2 identifies one way to rewrite the expression using the distributive property 2(9+3)

(2x9)-(2x3)

(2x9)+(9x3)

(2x9)+3
(2x9)+(2x3)

Question 3 simply using distributive property 7x48

(7x50)-(7x2)=350-14=336

(7x40)+8=288

(7x50)-2=348

(7x40)+(7x8)+7=343

Question 4 simplify using distributive property
9x81

(9x80)+1=721
(9x80)-(9x1)711
(9x80+(9x1)=729
(9x90)-(9x1)=801
please answer this 4 questions im stuck